Current management of stage IV nasopharyngeal carcinoma without distant metastasis. (April 2020) - Ng, Wai Tong; Corry, June; Langendijk, Johannes A.; Lee, Anne W.M.; Mäkitie, Antti; Mendenhall, William M.; Rinaldo, Alessandra; Rodrigo, Juan P.; Saba, Nabil F.; Smee, Robert; Strojan, Primož; Suárez, Carlos; et al.
Highlights: Review of the treatment paradigm for non-metastatic stage IV nasopharyngeal cancer. Describe the differential failure patterns, and suggest future treatment approaches. Summary of promising novel treatment techniques, and on-going clinical trials. Propose future research directions for this challenging disease entity. Abstract: Up to one in four patients with nasopharyngeal carcinoma present with non-metastatic stage IV disease (i.e. T4 or N3). Distinct failure patterns exist, despite the routine adoption of contemporary treatment modalities such as intensity modulated radiotherapy and systemic chemotherapy. Concurrent chemoradiotherapy (CCRT) followed by adjuvant chemotherapy or induction chemotherapy followed by CCRT are commonly employed in this setting, with the latter emerging as the preferred option. Additionally, emerging radiation technologies like proton therapy has become available offering new opportunities for prevention of radiation-induced side effects. This article reviews not only the current treatment strategies, but also discusses novel ways to tackle this challenging disease with respect to the patterns of failure.